Cameroon: The Law across the Bridge: Twenty Years (1972-1992) of Confusion - Ngwafor, Ephraim (Revue générale de droit, 1995)
As a result of its hi-jural legal system consisting of Common Law and Civil Law jurisdictions, Cameroon has been faced with some serious legal dilemmas. Amongst the problems that have arisen is the question of whether a judge in a Civil Law jurisdiction has the authority to judge a divorce matter where the parties to the action are domiciled in a Common Law jurisdiction and vice versa. This article aims to undertake an analysis of the legal system in Cameroon in an attempt to provide a solution to the foregoing issue.